Infundibulomatosis: A case report with immunohistochemical study and literature review. - Cardoso, JC (2010)
Tumor of the follicular infundibulum was first described in 1961 by Mehregan and Butler in a patient presenting with multiple papules. It is more frequent, however, as an isolated lesion affecting mainly the face, neck, and upper trunk. Clinical presentation is variable, requiring histology for the diagnosis, which reveals typically a plate-like proliferation of keratinocytes in continuity with the epidermis and hair follicles; some morphological features are reminiscent of the outer root sheath of the hair follicle. A well defined network of elastic fibers surrounding the tumor is usually present using the appropriate staining and this finding is specific because it is not found in other benign follicular tumors. Multiple infundibulomas are usually sporadic and there is no apparent association with internal malignancy. The authors report the case of a 30-year-old female patient with a 5-year history of multiple small discrete hypopigmented macules and papules, scattered over the submental and submaxillary regions and anterior neck. Histopathological findings were consistent with the diagnosis of tumor of the follicular infundibulum. Immunohistochemical study was performed to further characterize the proliferation.